Workshop International English Language Testing System (IELTS) bagi Mahasiswa dan Alumni Fresh Graduate Fakultas Teknik Gowa Universitas Hasanuddin - fauzan djamaluddin; Onny Sutresman; Ilyas Renreng (Faculty of Engineering UNHAS, 2020)
IELTS (International English Language Testing System) is a standardized English proficiency test which is a prerequisite for continuing study or work This workshop aims to assist the engineering faculty in its efforts to improve the mastery of English for new graduates which is designed and oriented towards mastering English with IELTS equivalents. This activity lasted for 3 days, from 28 to 30 August 2020. There were 20 (twenty) participants consisting of new graduates from the Hasanuddin University engineering faculty. Overall, the activities are expected to run smoothly and enthusiastically follow the Workshop process from beginning to end. The success of this program can also be seen from the achievement of predetermined success indicators, namely the number of participants who attended the workshop and the pre-test as expected, which exceeded 80% and 50%.